The emergy of metabolism in the same ecosystem (maize) under different environmental conditions. (1st August 2018) - Zhai, Xiajie; Zhao, Huan; Guo, Lizhu; Finch, Deborah M.; Huang, Ding; Liu, Kesi; Tang, Shiming; Yang, Yuejuan; Guo, Jianxin; Li, Jiahuan; Xie, Shu; Wang, Kun
Abstract: Ecosystem sustainability is the basis for life, economic and social sustainability. The energy metabolism of an ecosystem has long been a focus area in the scientific community because it determines the productivity, sustainability and development of ecosystem. This study applied emergy analysis to explore the metabolism of maize ecosystems under different environmental conditions; to investigate its energy input, environmental pressure and sustainability; and to understand the maintenance mechanism of the general ecosystem based on the China statistical data of 2014. Results showed that the sum of renewable natural resources ranged from 0.62 × 10 14 seJ/ha in Xinjiang to 6.34 × 10 14 seJ/ha in Guangxi; the sum of nonrenewable natural resources ranged from 3.95 × 10 14 seJ/ha for Henan to 9.46 × 10 14 seJ/ha for Jilin; the sum of purchased renewable resources ranged from 2.97 × 10 14 seJ/ha for Heilongjiang to 26.14 × 10 14 seJ/ha for Gansu; the sum of purchased nonrenewable resources ranged from 14.89 × 10 14 seJ/ha in Sichuan to 33.00 × 10 14 seJ/ha in Gansu. In addition, the environmental loading ratio in Xinjiang was the highest, followed by Ningxia (25.92), Gansu (24.77), Inner Mongolia (23.15), the lower values were 4.48, 4.21 and 4.00 for Guizhou, Chongqing and Guangxi, respectively; similarly, the emergy sustainability index in the provinces of southern China were higher than those in northwest of China. Above all, maize ecosystem is developed with a stronger competitive ability than other agricultural ecosystems, especially in the southern region of China, but also has a high environmental loading ratio. Furthermore, the proportion of natural and purchased emergy input ranged from 13.65% vs 86.35% in Xinjiang to 33.70% vs 66.30% in Heilongjiang, which were close to 30% vs 70%, 25% vs75%, 22% vs 78%, 20% vs 80% and 15% vs 85% for Northeast of China, Southwest of China, Loess Plateau, Huang-Huai-Hai Plain and Northwest of China respectively. Our study demonstrates that the natural energy in the maize ecosystem influenced the quantity and proportion of purchased energy. Different combinations of natural and purchased emergy were coupled to maintain the same ecosystem under the different environmental conditions. Its recommendation is to consider changing the crop production systems or artificial energy inputs in different regions based on differences in natural factors in order to make more efficient use of resources, reduce the use of chemical fertilizers, and promote the sustainability of ecosystems. Graphical abstract: Image Highlights: Maize ecosystems is more competitive than other agro-ecosystems, but it also has a high environmental loading ratio. Natural and purchased energy were coupled to maintain the same ecosystem under the different environmental conditions. The proportion of natural and purchased emergy input ranged from 30% vs 70% to 15% vs 85% for NE, SW, LP, HP and NW of China respectively.